1986
DOI: 10.1002/esp.3290110404
|View full text |Cite
|
Sign up to set email alerts
|

Corroded cobbles in Southern Death Valley: Their relationship to honeycomb weathering and lake shorelines

Abstract: In southern Death Valley, pits similar in morphology to honeycomb weathering (herein referred to as corrosion pits) occur on the surfaces ofcobbles that are associated with wave-produced benches. The pitted cobbles include a variety of igneous, metamorphic, and siliciclastic rocks; corrosion pits are rare to absent in limestones or dolomites. Pit morphology is controlled by cobble lithology. In massive rocks the pits are arcuate, elongate, and gently tapering; corrosion of laminated or foliated rocks has produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…For examples, disaggregation of grains and pore-infilling by salts may coincide with etching of quartz grains and feldspars (e.g., McGreevy and Smith, 1984;Butler and Mount, 1986). Salt weathering is not invariably the cause of tafoni formation, but salts are often present in tafoni backwalls and flakes and cause disintegration both through physical and chemical processes.…”
Section: The Single Process Modelmentioning
confidence: 97%
“…For examples, disaggregation of grains and pore-infilling by salts may coincide with etching of quartz grains and feldspars (e.g., McGreevy and Smith, 1984;Butler and Mount, 1986). Salt weathering is not invariably the cause of tafoni formation, but salts are often present in tafoni backwalls and flakes and cause disintegration both through physical and chemical processes.…”
Section: The Single Process Modelmentioning
confidence: 97%
“…This recognition that many 'characteristic' desert landforms are inherited features has not been so widely acknowledged in the study of smaller-scale weathering forms developed on outcrops and released debris. Yet scale differences should not preclude consideration that many smaller scale debris weathering forms may not be the direct product of the environmental conditions in which they are currently found (Butler and Mount, 1986) and, that past conditions may have a profound effect on the weathering response of debris to contemporary conditions.…”
Section: Introductionmentioning
confidence: 96%
“…This paper investigates rates of coastal denudation of greenschist in the supratidal zone on the Start-Prawle peninsula in south Devon, United Kingdom (Figure 1). The nature of the rock weathering processes operating in the study location is indicated by the abundance of honeycomb weathering patterns on exposed surfaces; these features are commonly regarded as indicative of weathering by salt crystallization (Bartrum, 1936;Mustoe, 1982Mustoe, , 1983McGreevey, 1985a;Butler and Mount, 1986). Studies by the present author (Mottershead, 1981(Mottershead, ,1982(Mottershead, ,1983 have demonstrated that rock denudation is indeed active, with a mean rate of surface lowering derived from 34 points over a one year period measured by micro-erosion meter (MEM) of 0.61 mm a-'.…”
Section: Introductionmentioning
confidence: 99%